Risk Attitudes with State-Dependent Indivisibilities in Consumption - Markus Fels (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Some consumption opportunities, e.g. medical treatments, are both indivisible and only valuable in particular states of nature. The existence of such state-dependent indivisible consumption opportunities influences a person's risk attitudes. In general, people are not risk averse anymore even if utility from divisible consumption is concave. I propose a definition of insurance in the context of state-dependent preferences and investigate the different motives underlying insurance demand. The same reasons that rule out risk aversion turn out to be the basis of a desire to insure.This calls into question the standard approach that bases insurance demand on risk aversion with important implications for policy and research.
Keywords: D01; D81; 330; Risk Preferences; Indivisible Consumption; Insurance; Gambling